The Determinant of Financial Statements-Content Information: Corporate Governance as a Mediating Variable - Nurohmi, Siti; Sutrisno, Sutrisno; Baridwan, Zaki (Universitas Negeri Malang, 2017)
This study aimed to examine the effect of human resource capacity, internal control, utilization of information technology and corporate governance of the financial statement information. Retrieving data using a survey method. The sample in this study is the head of the bureau, division chief, section chief, head of the sub-division and the administrative manager of financial spread in the working area of Perum Jasa Tirta I is Brantas River and Bengawan Solo. A total of 148 data processed using smartPLS. The results of this study indicate that the capacity of human resources and internal control affecting corporate governance, in addition to the capacity of human resources and corporate governance affects the financial statements information directly. The implication of this study is the management of Perum Jasa Tirta I must ensure that the human resources that exist in the company are resources that are competent and have sufficient internal control, so as to improve the implementation of corporate governance and financial reporting information delivered in a timely manner. Keywords: determinants of financial statements information, corporate governance.